Characterization of the volatile compounds and anatomical features in commercial samples of Echinodorus plant species (Research, Society and Development, 2020)
Echinodorus grandiflorus and Echinodorus macrophyllus are medicinal plants that are widely used in Brazilian folk medicine. The aims of this study were to evaluate the effect of oven drying with ventilation on the chromatographic profile of volatile compounds and to compare the leaf anatomy and volatile compounds of different commercial E. macrophyllus (Kunth) Micheli and E. grandiflorus Mich. Samples. The components found in fresh and dried samples were extracted by SPME and analysed by GC-MS, and the anatomical features of the leaves were observed microscopically. A total of 46 compounds were identified; five compounds were present in the dried and fresh samples of E. grandiflorus and all of the commercial samples. The anatomy analyses confirmed the authenticity of the species. Apparent differences in the volatile composition between the species were observed, allowing the identification of chemical marker. The results showed that commercial establishments do not conform to regulations, and the techniques used were effective for the characterization of volatile compounds and for quality control of medicinal plants.